2023
DOI: 10.3390/life13010229
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Maximum Tongue Force in Women Suffering from Chronic and Asymptomatic Temporomandibular Disorders—An Observational Study

Abstract: Background: Temporomandibular disorders are craniofacial disorders characterized by the presence of chronic pain in masticatory muscles, with higher incidence in the women population. There is little research that has studied tongue force related to temporomandibular disorders, but there are a lot of studies that have demonstrated the impact of tongue force in vital functions, such as chewing, swallowing, phonation, or breathing. According to this, the aim of this study was to compare the maximum force of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In this way, these cranial nerves control the muscles of mastication, facial gestures, and the tongue, respectively, in order to achieve the optimal functionality of the entire system during speech and mastication, among other functions. Additionally, we have already published an observational study which showed significant differences in the maximum tongue force between asymptomatic women and those with chronic temporomandibular disorder, corroborating the necessity for the assessment of the tongue force in this pathology [ 43 ]. In this article, a decrease in tongue strength of about 30% on average across all directions was found in the group of patients with chronic TMD.…”
Section: Discussionmentioning
confidence: 78%
“…In this way, these cranial nerves control the muscles of mastication, facial gestures, and the tongue, respectively, in order to achieve the optimal functionality of the entire system during speech and mastication, among other functions. Additionally, we have already published an observational study which showed significant differences in the maximum tongue force between asymptomatic women and those with chronic temporomandibular disorder, corroborating the necessity for the assessment of the tongue force in this pathology [ 43 ]. In this article, a decrease in tongue strength of about 30% on average across all directions was found in the group of patients with chronic TMD.…”
Section: Discussionmentioning
confidence: 78%